Kufrun Duna Kufrin, Terminologi Ibnu Abbas Membantah Sekte Takfiri - Luqman Abdul Jalal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The takfiri sect misunderstands infidel terminology (ghuluw fi at-takfir). Everyone who does not rule with what Allah has revealed is an infidel, apostate, out of the corridors of Islam. Contrary to the understanding of Ibn Abbas RA. and the majority of friends that the meaning of the word of Allah in the letter al-Ma'idah verse 44 is not a grand infidel, but a sinful act that does not cause the disbeliever to apostatize (kufrun duna kufrin). This research is a literature review, the author uses the method of library research or library research. The data sources in this study used authoritative classical and contemporary commentaries, and other sources relevant to the research. This study concludes that the terminology of Ibn Abbas RA.